Investigation of canine caudal articular process dysplasia of thoracic vertebrae using computed tomography: Prevalence and characteristics - Ban, Jiyoung; Park, Jihyeon; Kim, Hyesung; Yoon, Kwangyong; Oh, Miju; Lee, Yooyoung; Lee, Minju; Chang, Jinhwa; Kim, Byungjin; Kim, Jongman; Chang, Dongwoo (Frontiers in Veterinary Science, 2023)
Caudal articular process (CAP) dysplasia is a congenital vertebral malformation that results from the failure of ossification center of articular process located in vertebrae, which includes aplasia or hypoplasia. In previous studies, it was reported to be common in small and chondrodystrophic dogs however, investigated in limited breeds. So we aimed to confirm the prevalence and the characteristics of CAP dysplasia in various breeds, and also to investigate the association of CAP dysplasia and spinal cord myelopathy in neurologically abnormal dogs. In this multicenter, retrospective study, the clinical records and thoracic vertebral column computed tomographic (CT) images of 717 dogs between February 2016 and August 2021 were included and 119 dogs which also underwent magnetic resonance imaging (MRI) examination were evaluated. Overall, 337 of 717 dogs (47.0%) had at least one thoracic CAP dysplasia and the prevalence of CAP dysplasia was significantly higher in dogs with a lower body weight (P < 0.0001). A total of 66.4% of toy breeds, 39.0% of small breeds, 20.2% of medium breeds, and 6.0% of large breeds were affected by at least one CAP dysplasia. The most affected vertebra was T4 in toy (48.1%) and small breeds (20.8%), and T5 in medium (20.8%) and large breeds (5.0%). In all groups, prevalence of CAP dysplasia between T1 and T9 was higher than post-diaphragmatic vertebrae (T10–T13). Fifty nine of 119 dogs which underwent both CT and MRI examination had symptoms of spinal cord myelopathy of T3-L3 and twenty-five of 59 dogs (42.3%) had at least one thoracic CAP dysplasia. In that 25 neurologically abnormal dogs, 41 sites of intervertebral disc disease (IVDD) were detected. However, only one dog had both CAP dysplasia and herniated disc at the same level. Also, CAP dysplasia associated non-compressive spinal myelopathy at the same level was found in the other dog. Association CAP dysplasia with spinal myelopathy is speculated but is not confirmed by this study.